Posterior semicircular canal ossification following acute vestibular loss mimicking inferior vestibular neuritis: A case report - Comacchio, Francesco; Castellucci, Andrea (Frontiers in Neurology, 2022)
Vestibular neuritis (VN) mostly involves the superior vestibular nerve. Isolated inferior vestibular neuritis (IVN) has been more rarely described. The diagnosis of IVN is based on an abnormal head impulse test (HIT) for the posterior semicircular canal (PSC), pathological cervical vestibular-evoked myogenic potentials (C-VEMPs), and spontaneous downbeat nystagmus consistent with acute functional loss of inner ear sensors lying within the inferior part of the labyrinth. HIT for both lateral and superior semicircular canals is normal, as are ocular VEMPs and bithermal caloric irrigations. The etiology of IVN is debated since peripheral acute vestibular loss with a similar lesion pattern can often be associated with ipsilesional sudden hearing loss (HL). Viral inflammation of vestibular nerves is considered the most likely cause, although reports suggest that VN usually spares the inferior division. On the other hand, an ischemic lesion involving the terminal branches of the common cochlear artery has been hypothesized in cases with concurrent HL. Debated is also the lesion site in the case of IVN without HL since different instrumental patterns have been documented. Either isolated posterior ampullary nerve involvement presenting with selective PSC functional loss on video-HIT, or only saccular lesion with isolated ipsilesional C-VEMPs impairment, or inferior vestibular nerve damage (including both saccular and posterior ampullary afferents) exhibiting an impairment of both C-VEMPs and PSC-HIT. We report an interesting case of a patient with an acute vestibular loss consistent with IVN without HL who developed a PSC ossification on follow-up, questioning the viral origin of the lesion and rather orienting toward an occlusion of the posterior vestibular artery. To the best of our knowledge, this is the first report of PSC ossification after a clinical picture consistent with IVN.